1999
DOI: 10.1103/physrevlett.82.4647
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Hopf Bifurcations in Stratified Taylor-Couette Flow

Abstract: Experimental and theoretical results for the axially, stably stratified Taylor-Couette flow are presented. The primary instability is a direct Hopf bifurcation. It leads the system into an oscillatory state of confined internal waves, in good agreement with linear stability analysis. The secondary bifurcation, which leads the system to a pattern of drifting nonaxisymmetric vortices, is a subcritical Hopf bifurcation. This first experimental evidence of a global bifurcation is thought to be generic to dynamical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…They also show that the initial instability is axisymmetric, while non-axisymmetric motions appear only at a slightly higher Reynolds number than the critical one. Further studies of this problem are reported in Boubnov et al (1996), Boubnov & Hopfinger (1997), and Caton, Janiaud & Hopfinger (1999).…”
Section: Introductionmentioning
confidence: 85%
“…They also show that the initial instability is axisymmetric, while non-axisymmetric motions appear only at a slightly higher Reynolds number than the critical one. Further studies of this problem are reported in Boubnov et al (1996), Boubnov & Hopfinger (1997), and Caton, Janiaud & Hopfinger (1999).…”
Section: Introductionmentioning
confidence: 85%
“…Taylor–Couette flow (TCF) between two coaxial cylinders has been one of the paradigmatic flows for a long time, since it allows the study of various physical phenomena in fluid dynamics, such as flow instability and transition (Coles 1965; DiPrima, Eagles & Ng 1984; Marques & Lopez 1997; Caton, Janiaud & Hopfinger 1999; Hristova et al. 2002), nonlinear dynamics (Pfister & Rehberg 1981; Mullin, Cliffe & Pfister 1987), pattern formation (Andereck, Liu & Swinney 1986; Boubnov, Gledzer & Hopfinger 1995; Lim, Chew & Xiao 1998; Guillerm et al.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor-Couette flow (TCF) between two coaxial cylinders has been one of the paradigmatic flows for a long time, since it allows the study of various physical phenomena in fluid dynamics, such as flow instability and transition (Coles 1965;DiPrima, Eagles & Ng 1984;Marques & Lopez 1997;Caton, Janiaud & Hopfinger 1999;Hristova et al 2002), nonlinear dynamics (Pfister & Rehberg 1981;Mullin, Cliffe & Pfister 1987), pattern formation (Andereck, Liu & Swinney 1986;Boubnov, Gledzer & Hopfinger 1995;Lim, Chew & Xiao 1998;Guillerm et al 2015) and turbulence (Lathrop, Fineberg & Swinney 1992a,b;Huisman et al 2012;Grossmann, Lohse & Sun 2016). Moreover, flows of a dispersed phase (bubbles, drops or particles) and the migration behaviour of dispersions have been widely examined in the Taylor-Couette system due to numerous practical applications in chemical engineering, such as the oil industry, filtration and transformation of thermal energy (Chan & Leal 1981;Wereley & Lueptow 1999;Resende et al 2001;Rudman 2004;Climent, Simonnet & Magnaudet 2007).…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of [8], pre-2001 laboratory experiments on stratified Taylor-Couette flow were always carried out with a fixed outer cylinder [8][9][10][11][12] (so µ = 0 < η 2 ) and the relevance of the Rayleigh line was not questioned. The first experimental evidence of the SRI came in 2007 [13] where non-axisymmetric instability was clearly observed in the centrifugally-stable regime.…”
Section: Introductionmentioning
confidence: 99%